(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2026)
The aim of this research is to demonstrate the impact that inclusive leadership can have on achieving innovative marketing. The research relied on the independent variable, "inclusive leadership," with its three dimensions: openness, availability, and accessibility. The dependent variable, "innovative marketing," with its six dimensions—market technology, sustainable innovation, calculated risk, resource optimization, and customer value creation—was also considered. The research employed a descriptive-analytical approach. The research questions were addressed by testing several main and sub-hypotheses regarding correlation and influence. A questionnaire was designed to collect the necessary data, and a purposive sample of 90 participants was selected, representing administrative leaders and managers at the Open Education College. The statistical software SPSS version 27, Excel 2013, and SmartPLS version 4 were used to extract the results. This research reached a number of conclusions regarding leadership. The most prominent of these is that it has a continuous and effective positive impact resulting from its dimensions in achieving innovative marketing, which was represented by the validity of the research hypotheses and the validity of the hypothetical model with the existence of a relationship and impact of inclusive leadership in innovative marketing. The researchers concluded with a set of recommendations, the most important of which is forming a work team that includes employees who have a high level of capabilities to support the competitive process in the market through their contribution to providing new and creative ideas that contribute to the Open Educational College reaching its goals and achieving an excellent market position.